2010
DOI: 10.5380/acd.v11i2.21374
|View full text |Cite
|
Sign up to set email alerts
|

FITOQUÍMICA E ATIVIDADES BIOLÓGICAS DO GÊNERO Jatropha: MINI-REVISÃO

Abstract: O Gênero Jatropha, está inserido na família Euphorbiaceae. Esta família compreende 290 gêneros e aproximadamente 7500 espécies, distribuídas em todo o mundo, principalmente nas regiões tropicais. Os maiores centros de dispersão encontram-se nas Américas e na África. São plantas de hábito variado, existindo na forma de ervas, subarbustos, árvores e trepadeiras (JOLY, 1985).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
2
7
0
4
Order By: Relevance
“…19 As well as extracts of J. gossypiifolia presented activity against P. aeruginosa and Bacillus subtilis. 15 These results corroborate with another study that states that extracts of the genus Jatropha have antibacterial action. 17 Another study about the antimicrobial activity of the root, stem and leaf extracts of Croton pulegioides Baill, belonging to the same Jatropha family, concluded that the methanolic extract of the stem showed antimicrobial activity against the strains of S. aureus and S. epidermidis, while the methanolic extract of the leaves showed no activity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…19 As well as extracts of J. gossypiifolia presented activity against P. aeruginosa and Bacillus subtilis. 15 These results corroborate with another study that states that extracts of the genus Jatropha have antibacterial action. 17 Another study about the antimicrobial activity of the root, stem and leaf extracts of Croton pulegioides Baill, belonging to the same Jatropha family, concluded that the methanolic extract of the stem showed antimicrobial activity against the strains of S. aureus and S. epidermidis, while the methanolic extract of the leaves showed no activity.…”
Section: Discussionsupporting
confidence: 89%
“…These data corroborate with studies that carried out phytochemical prospecting with plants of the same genus, which identified the presence of alkaloids, tannins, flavonoids, steroids and saponins, these data are similar to those found in another study. [14][15] Another study found secondary metabolites such as tannins, flavonoids, steroids and saponins in the different parts of J. gossypiifolia, which corroborates this study. 6 However, metabolites such as terpenoids, quinones, lactones and lignans reported by other studies were not found in the extracts studied in this study.…”
Section:  In Vitro Healing Potential Using Scratch Assaysupporting
confidence: 84%
See 2 more Smart Citations
“…e Phyllanthaceae Martinov são amplamentes distribuídas, com maior diversidade em regiões tropicais (Judd et al, 2009), apresentando gêneros com representantes comumente utilizados na medicina popular. Em Euphorbiaceae, dentre os gêneros que possuem espécies medicinais, se encontram na literatura Croton L., Euphorbia L. (Mwine & Van Damme, 2011) e Jatropha L. (Hirota et al, 2010), e, em Phyllanthaceae, o gênero Phyllanthus L. (Souza & Lorenzi, 2005).…”
unclassified